Comparison of transcriptional profiles of Treponema pallidum during experimental infection of rabbits and in vitro culture: Highly similar, yet different. - Bridget D De Lay (Public Library of Science (PLoS), 2021)
Treponema pallidum ssp. pallidum, the causative agent of syphilis, can now be cultured continuously in vitro utilizing a tissue culture system, and the multiplication rates are similar to those obtained in experimental infection of rabbits. In this study, the RNA transcript profiles of the T. pallidum Nichols during in vitro culture and rabbit infection were compared to examine whether gene expression patterns differed in these two environments. To this end, RNA preparations were converted to cDNA and subjected to RNA-seq using high throughput Illumina sequencing; reverse transcriptase quantitative PCR was also performed on selected genes for validation of results. The transcript profiles in the in vivo and in vitro environments were remarkably similar, exhibiting a high degree of concordance overall. However, transcript levels of 94 genes (9%) out of the 1,063 predicted genes in the T. pallidum genome were significantly different during rabbit infection versus in vitro culture, varying by up to 8-fold in the two environments. Genes that exhibited significantly higher transcript levels during rabbit infection included those encoding multiple ribosomal proteins, several prominent membrane proteins, glycolysis-associated enzymes, replication initiator DnaA, rubredoxin, thioredoxin, two putative regulatory proteins, and proteins associated with solute transport. In vitro cultured T. pallidum had higher transcript levels of DNA repair proteins, cofactor synthesis enzymes, and several hypothetical proteins. The overall concordance of the transcript profiles may indicate that these environments are highly similar in terms of their effects on T. pallidum physiology and growth, and may also reflect a relatively low level of transcriptional regulation in this reduced genome organism.